The Changing Face of Little Italy: The Miss Colombo Pageant and the Making of Ethnicity in Trail, British Columbia, 1970–1977 - Fielding, Stephen (Urban History Review / Revue d'histoire urbaine, 2010)
This article examines gender and ethnicity as part of the same social experience. It argues that the annual contest to crown Miss Colombo in Trail, British Columbia, during the first half of the 1970s, together with the campaign to preserve the beauty pageant after 1973, offers a unique gendered context to understand the making of ethnicity in a small city. Broadly speaking, the pageant reflected specific social, economic, spatial, and cultural changes within the local Italian experience: a strong sense of place, occupational success, movement to ethnically mixed neighbourhoods, and positive relations with non-Italians. These processes played out in a paradoxical forum of the Colombo pageant—a paternal institution that celebrated and evaluated young Italian women’s bodies. Never contesting the institution itself, which carried a gendered power imbalance, Italian women—both as volunteers and contestants—worked through the pageant to promote their own interpretation of Italian belonging and to endorse a range of new possibilities for themselves. The women dramatically recast, but did not overturn, the gendered structures through which these changes took place—a pattern that points to the resiliency of paternalism in discourses of ethnic belonging.